Malaysia dalam hubungan kerjasama ekonomi intra-wilayah ASEAN (BIMP-EAGA) - Jennikson, Lojem (Universiti Malaysia Sarawak (UNIMAS), 1997)
BIMP-EAGA is ASEAN's third intra-regional economic cooperation after SIJORI and IMT-GT. This study examines the involvement of Malaysia (specifically East Malaysia) with other states participating in BIMP-EAGA. East Malaysia will be able to maximise its development potentials by participating in the growth triangle. This can be achieved by a common pooling of domestic economic resources such as forest resources, minerals and skills that complement the economics topography of other areas involved in BIMP-EAGA. In this context, Malaysia is and plans to establish bilateral and multilateral economic relations with other areas of BIMP-EAGA. Hitherto, Malaysia appears to be actively involved in different areas of cooperations in BIMP-EAGA, e. g; tourism, financial formation, agro-industry, human resource development and others. At present, some internal and external constraints appear to have restricted Malaysia's full involvement in all areas of cooperation in BIMPEAGA. In the long run, however, Malaysia is expected to play a more effective role in BIMP-EAGA, hopefully to help contribute to the realisation of bigger ASEAN economic project such as AFTA.